Pelatihan Inovasi Pembelajaran Berbasis Permainan Edukatif untuk Meningkatkan Karakter Siswa Sekolah Dasar - Amaliah, Nurhildha; Kurnia, St. Alyah; Maharani; Haris, Sitti Ariqah Azka; Wahyu, Andra Saputra; Poerwanto, Bobby (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
This activity explores the development and implementation of “Moral Quests,” an educational game designed to enhance the character development of elementary school students at SD Inpres Sero by adapting Indonesian folklore. The significance of this community engagement project lies in creating an innovative educational tool that instills moral values in young learners—an essential aspect of their holistic development. The topic is highly relevant as it leverages cultural heritage, specifically Indonesian folktales, to make learning engaging and meaningful. The community engagement project employs a participatory approach, involving teachers, students, and community members during the design and implementation phases to ensure cultural relevance and educational effectiveness. The methodology includes storytelling, interactive games, and character-building activities to achieve its objectives. The results demonstrate a significant improvement in students’ understanding and application of core moral values such as honesty, responsibility, and respect. These findings underscore the potential of culturally adapted educational games in nurturing desired character traits among young learners. In conclusion, this project emphasizes the importance of integrating cultural elements into educational tools to enhance their impact and relevance, pointing toward a positive future for character development.